Anamorphic zoom system based on liquid crystal displays - Iemmi, C. (2009)
In this work we present an anamorphic zoom system, based on liquid crystal displays, which allows changing the magnification and distortion of an image very quickly, without mechanical parts and keeping the output plane stationary. The anamorphic lenses that make up the optical processor are obtained by displaying a combination of convergent-divergent cylindrical lenses, with arbitrary orientations, onto the spatial light modulators. In order to illustrate the capabilities of the system, some experimental results are shown.